Partial cross ownership and collusion - Samuel de Haas; Johannes Paha (Philipps-University Marburg, School of Business and Economics, 2016)
This article finds that non-controlling minority shareholdings among competitors lower the sustainability of collusion. This is the case under an even greater variety of situations than was indicated by earlier literature. The collusion destabilizing effect of minority shareholdings is mainly caused by their unilateral effects, and it is particularly prevalent in the presence of an effective antitrust authority.
Keywords: G34; K21; L41; 330; Collusion; Coordinated Effects; Minority Shareholdings; Merger Control; Unilateral Effects